2020
DOI: 10.1590/0034-7167-2019-0430
|View full text |Cite
|
Sign up to set email alerts
|

Association between knowledge and adherence to foot self-care practices performed by diabetics

Abstract: Objectives: to verify the association between knowledge and adherence to foot self-care practices performed by patients with diabetes mellitus type 2. Methods: cross-sectional, descriptive study carried out with 197 patients in basic health units located in the Northeast region of Brazil. For data collection, we used a semi-structured questionnaire that addressed issues inherent to knowledge and Diabetes Self-Care Activities. Results: we observed that patients with moderate knowledge about self-care practice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 15 publications
2
24
0
9
Order By: Relevance
“…The report on a foot care task force conducted by the American Diabetes Association stressed the importance of health service users with DM having their feet assessed at least once a year and recognizing signs of possible complications to reduce lower limb amputations [ 26 ]. Batista et al [ 27 ] showed that low education levels hinder appropriate feet care, mainly due to reduced understanding of the disease and guidance given. For this reason, this type of advice should be clearly and objectively given.…”
Section: Discussionmentioning
confidence: 99%
“…The report on a foot care task force conducted by the American Diabetes Association stressed the importance of health service users with DM having their feet assessed at least once a year and recognizing signs of possible complications to reduce lower limb amputations [ 26 ]. Batista et al [ 27 ] showed that low education levels hinder appropriate feet care, mainly due to reduced understanding of the disease and guidance given. For this reason, this type of advice should be clearly and objectively given.…”
Section: Discussionmentioning
confidence: 99%
“…Realizar estas acciones de cuidado de los pies es importante para prevenir sequedad de la piel y aparición de fisuras, que constituyen vías de ingreso al desarrollo de procesos infecciosos y a la aparición de lesiones tisulares 15 . Dichas acciones de cuidado pueden reducir el riesgo de infección y, consecuentemente, el desarrollo del pie diabético, que en conjunto representan una de las principales causas de amputaciones en extremidades inferiores 16 . Por ese motivo, es esencial que los pacientes con DM conozcan las acciones de cuidado de los pies para minimizar la incidencia de complicaciones.…”
Section: Discussionunclassified
“…Similarly, a research (20) carried out in the Teresina, in the state of Piauí (PI),indicated a significant relation between the guidance made available by nurses to those with diabetes and the adherence to the activity of foot care. Therefore, the essence for the adherence to self-care, and, therefore, for the prevention against changes in the feet of those with diabetes, is correlated with the knowledge about the disease (21) . As a result, the positive repercussions of the follow up of this professional in the self-care of people with diabetes are reiterated, considering the benefits of sharing educational guidance.…”
Section: Variablesmentioning
confidence: 99%